PERANCANGAN SMART HYDROPONICS INDOOR PENANAMAN PAKCOY OTOMATIS BERBASIS PROGRAMMABLE LOGIC CONTROLLER - Izzahilmanisa, n/a; Muslim, Muhammad Aziz; Rusli, Moch. (Jurnal Mahasiswa TEUB, 2023)
The rapid rate of population growth in urban areas, especially, can cause environmental problems, one of which is a decrease in the availability of agricultural land. On the other hand, global problems such as changes in world temperature and extreme climate change can disrupt stability in maintaining food availability. In this millennial period, many businesses have developed to fulfill their own food needs, starting from the application of theory to technology. One method that is being widely used by farmers in Indonesia is hydroponics. The research, which was conducted in a closed room in a house in Mojokerto for 10 days, experimented with growing pakcoy hydroponically using several control integrations in the form of indoor photosynthesis, automatic nutrient dosing, liquid level monitoring, and air circulation regulation. Based on the implementation of the research using a programmable logic controller, which compared the results of indoor and outdoor planting, it was found that the temperature of the planting environment and the temperature of the water in the indoor growing media remained in the range of 24℃-29℃, the air humidity was 63% -96%, the nutrient density was 789-1298 PPM, and leaf growth of 1-2 strands per day. Yields of pakcoy plants on indoor growing media give maximum results on leaf growth and leaf color, but are not better than pakcoy plants on outdoor growing media or those exposed to direct sunlight. Keywords: PLC, hydroponic, indoor, pakcoy, automatic.